CAT102 - Introduction to Logic and Abstraction August/September 1998 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1998)
Bachelor of Computer Science (Hons) External Degree USM Programme (In Collaboration with Universiti Sains Malaysia)